|x+3/1,5| -5/6 = 0
Giúp mik nhanh nhé!!!
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\Leftrightarrow-\dfrac{2}{5}\left(4x-3\right)^2=-\dfrac{5}{18}\)
\(\Leftrightarrow\left(4x-3\right)^2=\dfrac{25}{36}\)
\(\Leftrightarrow4x-3\in\left\{\dfrac{5}{6};-\dfrac{5}{6}\right\}\)
hay \(x\in\left\{\dfrac{23}{24};\dfrac{13}{24}\right\}\)
\(a,\Leftrightarrow25x^2-70x+49-25x^2=32\\ \Leftrightarrow-70x=-17\Leftrightarrow x=\dfrac{17}{70}\\ b,\Leftrightarrow x^2-6x+9+x^2+2x+1-5=0\\ \Leftrightarrow2x^2-4x+5=0\\ \Leftrightarrow2\left(x^2-2x+1\right)+3=0\\ \Leftrightarrow2\left(x-1\right)^2=-3\Leftrightarrow\left(x-1\right)^2=-\dfrac{3}{2}\left(\text{vô lí}\right)\\ \Leftrightarrow x\in\varnothing\)
a, 2/3 - 2/9 + 7/9 = 6/9 - 2/9 + 7/9 = 10/9
b, 7/6 + 3/5 : 6 = 7/6 + 3/5 x 1/6 = 7/6 + 1/10 = 70/60 + 6/10 = 76/10 = 38/5
c, x : 6/25 = 18
x = 18 x 6/25
x = 36/25
d, ( 2/5 + 4/7) : x = 17/5
29/35 : x = 17/5
x = 29/35 : 17/5
x = 29/119
\(a.\dfrac{2}{3}-\dfrac{2}{9}+\dfrac{7}{9}=\dfrac{6}{9}-\dfrac{2}{9}+\dfrac{7}{9}=\dfrac{4}{9}+\dfrac{7}{9}=\dfrac{11}{9}\\ b.\dfrac{7}{6}+\dfrac{3}{5}:6=\dfrac{7}{6}+\dfrac{3}{5}\times\dfrac{1}{6}=\dfrac{7}{6}+\dfrac{1}{10}=\dfrac{70}{60}+\dfrac{6}{60}=\dfrac{76}{60}=\dfrac{19}{15}\\ c.x:\dfrac{6}{25}=18\\ x=18\times\dfrac{6}{25}\\ x=\dfrac{108}{25}\\ d.\left(\dfrac{2}{5}+\dfrac{4}{7}\right):x=\dfrac{17}{5}\\ \dfrac{34}{35}:x=\dfrac{7}{5}\\ x=\dfrac{34}{35}:\dfrac{7}{5}\\ x=\dfrac{34}{49}\)
\(x^5+x^4+x+1=0\)
\(\Leftrightarrow x+1=0\)
hay x=-1
`5/(-x^2+5x-6)+(x+3)/(2-x)=0`
Đk:`x ne 2,x ne 3`
`pt<=>-5/(x^2-5x+6)-(x+3)/(x-2)=0`
`<=>-5-(x+3)(x-3)=0`
`<=>(x+3)(x-3)=-5`
`<=>x^2-9=-5`
`<=>x^2-4=0`
`<=>(x-2)(x+2)=0`
`x ne 2=>x-2 ne 0`
`<=>x+2=0`
`<=>x=-2`
Vậy `S={-2}`
\(A=x^3-2x+n\)
\(B=n-2\)
\(A\text{⋮}B\) ⇒ \(\left(x^3-2x+n\right)\text{⋮}\left(n-2\right)\)
⇒ \(\left[\left(x^3-2x^2\right)+\left(2x^2-4x\right)+\left(2x-4\right)+\left(n+4\right)\right]\text{⋮}\left(n-2\right)\)
⇒ \(\left[x^2\left(x-2\right)+2x\left(x-2\right)+2\left(x-2\right)+\left(n+4\right)\right]\text{⋮}\left(n-2\right)\)
⇒ \(\left[\left(x-2\right)\left(x^2+2x+2\right)+\left(n+4\right)\right]\text{⋮}\left(x-2\right)\)
Vì \(\left(x-2\right)\left(x^2+2x+2\right)\text{⋮}\left(n-2\right)\)
Để \(A\text{⋮}B\)
⇒ \(n+4=0\)
⇒ \(n=-4\)
a: =>7(x-5)>0
=>x-5>0
=>x>5
b: =>x-1 thuộc {1;-1;11;-11}
=>x thuộc {2;0;12;-10}
c: =>x+1+7 chia hết cho x+1
=>x+1 thuộc {1;-1;7;-7}
=>x thuộc {0;-2;6;-8}
d: =>(x+2)(x-5)<0
=>-2<x<5